The Positive and Negative Experiences of Caregiving for Siblings of Young People with First Episode Psychosis - Bowman, Siann; Alvarez-Jimenez, Mario; Wade, Darryl; Howie, Linsey; McGorry, Patrick (Frontiers in Psychology, 2017)
Background: The impact of first episode psychosis (FEP) upon parents’ experience of caregiving has been well documented. However, the determinants and nature of this remain poorly understood in siblings. It is hypothesized that siblings of young people with FEP are also impacted by caregiving and burden. This study aimed to characterize the experience of caregiving for siblings of young people with FEP. Method: Survey methodology was used to explore the experience of 157 siblings in the first 18 months of their brother or sister’s treatment for FEP. Participants reported on their appraisal of the negative and positive aspects of caregiving as measured by the Experience of Caregiving Inventory (ECI). Descriptive statistics were used to establish the results for the total sample as well as for gender and birth order differences. A series of multivariate regression analyses were conducted to determine the relationships between illness characteristics and siblings’ experience of caregiving. Results: Older brothers reported the lowest scores for negative experiences in caregiving and younger sisters reported the highest. Negative experiences in caregiving resulted in less warmth within the sibling relationship and impacted negatively upon quality of life. When the young person with FEP had attempted suicide and/or been physically violent, siblings experienced more caregiver burden. Multivariate analysis showed that female gender was a significant factor in explaining the impact of illness related variables on the experience of caregiving. Conclusions: Suicide attempts and a history of violence resulted in higher caregiving burden for siblings regardless of whether they lived with the young person experiencing FEP or not. Female siblings are at higher risk of negative experiences from caregiving resulting in a reduced quality of life and a changed sibling relationship. Suicide attempts and violence are indicators for intensive case management to improve outcomes for the individual with FEP which may in turn reduce the burden experienced by the sibling. Clinicians can use these findings to identify siblings, assertively intervene and provide increased psychological support, psychoeducation and practical problem solving to reduce the burden. The caregiving role that they already play for their ill brother or sister should be recognized.